Can you afford to be ill : hospital service plan (London : The London Association for Hospital Services Limited)
1945 1945 1940s 15 pages : illustrations The London Association for Hospital Services Ltd A Company Limited by Guarantee (and not for profit) and sponsored by King Edward's Hospital Fund for London Chairman : SIR BERNARD DOCKER, K.B.E., J.P. Hospital Member Council of Management : COMDR. THE RT. HON. LORD GIFFORD, R.N. Hospital Member SIR HUGH LETT, BT., C.B.E., M.B., CH.B., F.R.C.S. Medical Member GENERAL SIR KENNETH WIGRAM, G.C.B., C.S.I. C.B.E., D.S.O. Hospital Member SIR EDWARD PEACOCK, G.C.V.O. Hospital Member SIR HAROLD WERNHER, K.C.V.O. Hospital Member SIR ERNEST POOLEY, K.C.V.O., M.A., LL.B. Hospital Member Dr. W. RUSSELL BRAIN, F.R.C.P. Medical Member Dr. CHARLES HILL, M.A., D.PH. Medical Member B. LEES READ, ESQ., A.C.A., F.H.A. Hospital Member S.W. BARNES, ESQ., F.H.A. Hospital Member SYDNEY GARBUTT, ESQ., F.H.A. Hospital Member Hon. Solicitors : MESSRS. E.F. TURNER & SONS. Medical Referee : S.H. WASS. ESQ., M.S., F.R.C.S. Auditors : MESSRS. DELOITTE, PLENDER, GRIFFITHS & Co. Bankers : BARCLAYS BANK LTD., 72 Cheapside, E.C.2. Registered Office: 10 OLD JEWRY, LONDON, E.C.2. Telephone : CLErkenwell 7261-2. 292/842/2/63